Integrated education as a solution for educational dualism from Said Nursi’s perspective - Rahimah, Embong; Najihah, Abd Wahid; Fadzli, Adam; Mohd Ridhuan Tee, Abdullah; Syed Hadzrullathfi, Syed Omar; Amilah Awang, Abdul Rahman; Rosnani, Hashim (2017)
This paper aims to analyze the concept of integrated curriculum and its processes based on an educational model proposed by Badiuzzaman Said Nursi (1877-1960) that is Madrasah alZahra. It attempts to help in deriving some possible answers as solution of educational dualism facing the Ummah today. Hence, Said Nursi’s life and works especially Risale-i Nur should be examined analytically. It is a fact that the Ummatic malaise is rooted from educational dualism, co-existence of traditional religious and modern secular systems of education as a negative impact of Western colonialization and secularization. In the twentieth century, many prominent civilizational reformists had attempted to revive Islamic civilization through the integration of knowledge. The integration of both traditional religious and modern secular sciences into an integrated curriculum is viewed as the best solution to resolve this critical problem among contemporary Muslim scholars including Said Nursi. It is found that Madrasah Zahra model proposed by Nursi manifests integration of knowledge in the sense that the positive sciences should be taught in the religious schools meanwhile religious subjects in the secular schools. This to make sure the products of religious education system are preserved from religious intolerance whereas the products of secular one from irreligious ethics. Integrated curriculum represents the epistemological aspect of Islamic education is a great challenge. The distinguished educational features of Madrasah al-Zahra model make it the most feasible model for Muslims to help in resolving its malaise of educational dualism in this current global context. Said Nursi’s educational thoughts and his Madrasah al-Zahra model give some implications in remodeling Islamic integrated curriculum for Islamic educational institutions in the effort of empowering Islamic education and then, reviving Islamic civilization.